2007
DOI: 10.1094/phyto-97-2-0132
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nested Polymerase Chain Reaction Detection ofMycosphaerellaspp. and Its Application to the Study of Leaf Disease inEucalyptusPlantations

Abstract: Glen, M., Smith, A. H., Langrell, S. R. H., and Mohammed, C. L. 2007. Development of nested polymerase chain reaction detection of Mycosphaerella spp. and its application to the study of leaf disease in Eucalyptus plantations. Phytopathology 97:132-144.Mycosphaerella leaf disease (MLD) is a serious disease of two of the major eucalypt species grown in temperate regions worldwide, Eucalyptus globulus and E. nitens. More than 30 species of Mycosphaerella have been reported on eucalypts worldwide. Accurate, rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 68 publications
(78 reference statements)
1
29
0
Order By: Relevance
“…Morphological assignment of Teratosphaeria species from typical necrotic leaf lesions on leaves collected from each trial indicated that T. cryptica was the principal lesion-causing species in the studied trials, followed by T. nubilosa. Nested polymerase chain reaction detection using infected leaves (Glen et al, 2007) confirmed this and revealed the additional presence of T. vespa, T. parva and T. tasmaniensis in most trials.…”
Section: Traits Assessedmentioning
confidence: 56%
See 1 more Smart Citation
“…Morphological assignment of Teratosphaeria species from typical necrotic leaf lesions on leaves collected from each trial indicated that T. cryptica was the principal lesion-causing species in the studied trials, followed by T. nubilosa. Nested polymerase chain reaction detection using infected leaves (Glen et al, 2007) confirmed this and revealed the additional presence of T. vespa, T. parva and T. tasmaniensis in most trials.…”
Section: Traits Assessedmentioning
confidence: 56%
“…The most obvious symptoms of MLD are necrotic leaf spots that grow in size and can coalesce to form large blotches. Such lesions may be occupied, and/or caused by, more than one Teratosphaeria species (Glen et al, 2007). MLD lesions reduce the photosynthetic capacity of trees, can lead to premature leaf abscission and, in extreme cases, severe defoliation, affecting both growth and tree form (Mohammed et al, 2003).…”
Section: Study Systemmentioning
confidence: 99%
“…The nuclear rDNA region, b-tubulin gene, and an ascomycete mating-type gene are the most common DNA sequences used for these purposes as their characteristics allow the identification of pathogens at species level. The ITS region is the most widely sequenced region and has been used to design speciesspecific primers to unequivocally detect the presence of the species of interest, as reported for some fungal species [17][18][19][20] as well as Colletotrichum acutatum, C. gloeosporioides, and C. coccodes [21,22]. In this study, speciesspecific primers were designed with the aim of developing a reliable, rapid, and sensitive method to specifically detect C. capsici.…”
Section: Introductionmentioning
confidence: 99%
“…It will, therefore, be necessary to reexamine all previous disease situations and tree improvement studies (e.g., Carnegie and Ades 2003;Carnegie et al 1994Carnegie et al , 1998 where T. nubilosa sensu lato has been implicated and to determine whether there might be differences in the host range and ecology of the two pathogens. This should not be difficult because the four fixed nucleotide characters in the ITS gene region are diagnostic and for many previous studies, sequence data are available in GenBank (Crous et al 2004;Glen et al 2007;Hunter et al 2004bHunter et al , 2009Kularatne et al 2004;Maxwell et al 2001;Pérez et al 2009a, b). Likewise, microsatellite data used on population studies (Pérez et al 2012;Hunter et al 2008Hunter et al , 2009 should also make it possible to determine which species was treated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Countries or continents where only T. pseudonubilosa was found include New Zealand, Western Australia and Tasmania (Crous et al 2004;Glen et al 2007;Hunter et al 2009;Kularatne et al 2004;Maxwell et al 2001;Pérez et al 2012). Likewise, areas where only T. nubilosa was found include New South Wales, Africa, Europe and South America (Carnegie 2007a;Crous et al 2004;Hunter et al 2004bHunter et al , 2009Pérez et al 2009aPérez et al , b, 2012.…”
Section: Discussionmentioning
confidence: 99%